THE VARIATION OF INTERPERSONAL MEANING BREADTH OF BILINGUAL TEXT “SERIBU KUNANG-KUNANG DI MANHATTAN BY UMAR KHAYAM” - Eka Yunita Liambo (PRASASTI: Journal of Linguistics, 2018)
ABSTRACTThe process of meaning realization to the target language may involve the change of meaning. This change leads to the variation of meaning depth, breadth, and height. This is caused by the differences of linguistic features between the target language and source language. Therefore, the difficulties of finding equivalent words in target language may force translators to use other words which do not have the exactly similar meaning. However, this becomes a phenomenon in translation studies. This research aims to know the variation of interpersonal meaning breadth of a bilingual text. The primary data of this research is the sentences of first bilingual text taken from Seribu Kunang-Kunang di Manhattan translated into A Thousand Fireflies in Manhattan. There were 281 sentences are analysed. The result shows that those sentences found to have different variations. The most frequently variations found in this short story are the first variations in which element functions in the source text and target text have one difference. First variation has 28,82% then followed by zero variation  with 23,48%. Whereas other sentences is classified as the second, third, fourth, fifth and sixth variation of interpersonal meaning breadth with percentage of 18,14%, 4,62%, 3,20%, 14,23% and 7,47%. These variations occurring in the first bilingual text Seribu Kunang-Kunang di Manhattan translated into A Thousand Fireflies in Manhattan seems to be done to maintain the correspondence in the target language.Keywords: bilingual, breadth meaning, interpersonal, translation, variation of meaning,